ANALISIS RESEPSI TERHADAP PERNYATAAN DR. LOUIS OWIEN TERKAIT COVID-19 (Studi Resepsi Penonton Hotman Paris Show dalam Mempersepsi Konten Pernyataan dr. Louis Terkait COVID-19) - Schavira Bakhita Auditama (2023)
The study explored a case of media report regarding controversial statements made by dr. Louis Owien, a figure claiming to be a doctor at the height of covid-19 pandemic. The statement that dr. Louis gave was regarding her disbelief in the presence of COVID-19 and deaths that occurred due to interactions between drugs, these two statements attracted the attention of the public, until finally dr. Louis was invited to the Hotman Paris Show to talk about other things related to COVID-19. The study aimed to explore audience's interpretation of dr. Louis Owien's statements given at the Hotman Paris show. This study uses the encoding-decoding theory from Stuart Hall,. This theory talks about the meaning of information by the communicant may be different from what is conveyed by the communicator. The research method used is descriptive qualitative using primary data sources in the form of Hotman Paris Show and interviews with informants as well as secondary data in the form of previous research, books and journals with similar topics. Data was colleted through in depth interview. The author applied M. K. Halliday's model of discourse analysis to determine preferred reading, which has three elements, namely the field of discourse, the participants of the discourse and the means of discourse to determine preferred reading delivered by dr. Louis on the Hotman Paris Show. Meanwhile, to explore participant's interpretation, the author employed in-depth interview. The position of meaning found in this study is negotiation, this is obtained from all the meanings that have been studied by informants. There were no informants who occupied the position of dominant hegemony meaning and there were also no informants who occupied oppositional meaning positions. Several factor that were often found to underlie participant's interpretation were mindset, education background, experience, value, general knowledge, and religius belief.